Recovering Stephen Leacock: "Sunshine Sketches of a Little Town" and the cultural production of value. - Meakin, Jonathan M. (University of Ottawa (Canada), 1998)
The central aim of Recovering Stephen Leacock: Sunshine Sketches of a Little Town and the Cultural Production of Value is simultaneously to rupture Leacock's canonized cultural signature and to recover the complexity of his cultural work. To this end, the present study maps Leacock's complexity as an antimodernist discourse of "accommodation and protest" in response to the cultural tensions of the late nineteenth- and twentieth-centuries. Moreover, through the conceptual model of Pierre Bourdieu's field of cultural production, this study explores how Leacock's antimodernist complexity is encoded in the production of his antimodernist discourse, career, texts--his cultural work--and the cultural authority and value invested in that work. The Introduction provides a critical survey of Leacock's production and reception, and outlines the relevance of T. J. Jackson Lears' notion of antimodernism, and Pierre Bourdieu's field of cultural production, to Leacock studies. Chapter One, "Discourse: Visionary and Reactionary--Leacock as an Antimodernist" discusses Leacock's work as an interdisciplinary antimodernist discourse of cultural authority and value. Chapter Two, "Career: The Perfect Salesman and A Cultural Authority," explores Leacock's careers as a professional writer and academic in terms of his antimodernist negotiation of authority and value. Chapter Three, "Text: Antimodernist Sketches of a Little Town," provides a test-case reading of Sunshine Sketches of a Little Town as an antimodernist text that reflects a number of Leacock's concerns towards the realization of social justice. Finally, the Conclusion intimates how this present study as a whole underscores the need, and highlights the possibility, of reading Leacock in terms of broader, international literary-historical periods.
Keywords: Literature, Canadian (English).